Prosocial behaviors and economic performance: Evidence from an online mental healthcare platform - Yan, Zhijun; Kuang, Lini; Qiu, Liangfei (Production and Operations Management, 2022)
With the growth of online mental healthcare platforms, health professionals have been providing online consultation services during their spare time. However, little is known about the prosocial behaviors of health professionals on these platforms and their effect on professionals’ economic performance. In this research, we aim to identify and quantify the main effect of prosocial behaviors (i.e., offering free services) on future economic performance and the potential mediation effects of relationship capital and reputation capital in an online mental healthcare platform. Based on signaling and commitment theories, we use a panel dataset from a Chinese online mental healthcare platform to test our hypotheses. Our findings show that a mental health professional's previous prosocial behavior has a positive impact on economic performance and that this effect may manifest through the relationship capital pathway. However, reputation capital generated from prosocial behaviors does not significantly mediate the impact of prosocial behavior on economic performance. Our research provides important implications for healthcare operations concerning service offerings and healthcare providers’ performance on online mental healthcare platforms.